Tinjauan Kritis Terhadap Penerapan Akad Murabahah di Koperasi Serba Usaha (KSU) Tunas Mulia Mandiri - Umi Alfiati; Dedy Rachmad (IRTIQO' : Postgraduate Journal of Islamic Economics, Finance and Accounting Studies, 2025)
Murabahah is a sale and purchase agreement for goods with a selling price consisting of the cost of purchasing the goods plus a profit margin that has been mutually agreed between the seller and the buyer. The principle of transparency requires sellers to inform buyers of the cost of purchasing the goods. This research aims to analyze the implementation of the murabahah contract at KSU Tunas Mulia Mandiri and understand its flexibility in non-shariah financial institutions. The research method used is descriptive qualitative. Data was collected through in-depth interviews with KSU Tunas Mulia Mandiri managers and supported by relevant literature reviews. The research results show that the murabahah financing practices carried out by KSU-TMM generally comply with sharia provisions and standards set by AAOIFI. However, there were findings that the implementation of the murabahah contract was not fully in accordance with the rules, namely that the contract should be carried out after the goods which are the object of the contract are fully owned by KSU-TMM. Apart from that, the initial agreement procedure (waad) with the customer before executing the contract has also not been implemented.